2012
DOI: 10.7763/ijapm.2012.v2.128
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Microfibril Angle and Tree Age in Acacia Mangium Wood Using X-Ray Diffraction Technique

Abstract: Abstract-The objective of this research is to suggest a regression models on the age-affecting and microfibril angle in Acacia mangium wood. Farther objective is to estimate the optimum age which produce fully crystalline cellulose in Acacia mangium wood. The term microfibril angle (MFA) in wood refers to the angle between the spiralling cellulose fibrils and the long axis of the tracheid cell wall. Acacia mangium wood was chosen for experimental data. In this study, the main MFA of the cell walls were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…ex Loud.) (Wang and Stewart 2012) and Acacia mangium (Abdullah et al 2010;Tabet et al 2012), where cambial age and height in the stem have been identified as the main contributors to variation. An early attempt to describe MFA variation in radiata pine was a model based on data from polarised light studies (Tian and Cown 1995).…”
Section: Introductionmentioning
confidence: 99%
“…ex Loud.) (Wang and Stewart 2012) and Acacia mangium (Abdullah et al 2010;Tabet et al 2012), where cambial age and height in the stem have been identified as the main contributors to variation. An early attempt to describe MFA variation in radiata pine was a model based on data from polarised light studies (Tian and Cown 1995).…”
Section: Introductionmentioning
confidence: 99%
“…MFA in wood science refers to the angle of the cellulose microfibrils to the direction of the axis of the cell (Tabet and Aziz 2010). In the S2 (secondary cell wall), the orientation angle of microfibrils in juvenile wood will be greater than in mature wood.…”
Section: Microfibril Angle (Mfa)mentioning
confidence: 99%